RAPID RESPONSE FROM BMJ.COM. Issue 7530 (15th December 2005) - Coenen, Samuel; Monnet, Dominique L; Ferech, Matus; Goossens, Herman
Abstract : Following is an edited excerpt from Rapid Responses generated by this article, all of which can be read in their entirety at http://bmj.bmjjournals.com/cgi/eletters/331/7520/815#120258 .—Editor